2013
DOI: 10.1088/0004-637x/773/2/109
|View full text |Cite
|
Sign up to set email alerts
|

Ketene Formation in Interstellar Ices: A Laboratory Study

Abstract: The formation of ketene (H 2 CCO, ethenone) in polar and apolar ices was studied with in situ 0.8 MeV proton irradiation, far-UV photolysis, and infrared spectroscopic analyses at 10-20 K. Using isotopically enriched reagents, unequivocal evidence was obtained for ketene synthesis in H 2 O-rich and CO 2 -rich ices, and several reaction products were identified. Results from scavenging experiments suggested that ketene was formed by free-radical pathways, as opposed to acid-base processes or redox reactions. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 64 publications
8
52
1
Order By: Relevance
“…2 and clearly shows the spectral redshift corresponding to species' C 18 O vibrational modes. Besides H 2 18 O 2 signals (i.e., 1384 and 832 cm −1 ), IR features of CH 2 C 18 O (ν 2 ), CH 3 CH 18 O (ν 4 ), CH 2 CH 18 OH (ν 9 ), and CH 3 CH 2 18 OH (ν 11 ) are found at 2106, 1677, 1114, and 1030 cm −1 , respectively (Hawkins & Andrews 1983;Rodler et al 1984;Hudson & Loeffler 2013;Maity et al 2014;Bergner et al 2019). Peak positions due to transitions not directly affected by O-atoms, such as the C-C stretching modes (1662 and 1639 cm −1 ) of CH 2 CH 18 OH and the CH 3 deformation (1351 cm −1 ) as well as the C-C stretching (1133 cm −1 ) mode of CH 3 CH 18 O do not shift more than the 1 cm −1 with respect to the same transitions of the main isotope, which is within our spectral resolution (Rodler et al 1984;Hawkins & Andrews 1983).…”
Section: Com Formation In Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and clearly shows the spectral redshift corresponding to species' C 18 O vibrational modes. Besides H 2 18 O 2 signals (i.e., 1384 and 832 cm −1 ), IR features of CH 2 C 18 O (ν 2 ), CH 3 CH 18 O (ν 4 ), CH 2 CH 18 OH (ν 9 ), and CH 3 CH 2 18 OH (ν 11 ) are found at 2106, 1677, 1114, and 1030 cm −1 , respectively (Hawkins & Andrews 1983;Rodler et al 1984;Hudson & Loeffler 2013;Maity et al 2014;Bergner et al 2019). Peak positions due to transitions not directly affected by O-atoms, such as the C-C stretching modes (1662 and 1639 cm −1 ) of CH 2 CH 18 OH and the CH 3 deformation (1351 cm −1 ) as well as the C-C stretching (1133 cm −1 ) mode of CH 3 CH 18 O do not shift more than the 1 cm −1 with respect to the same transitions of the main isotope, which is within our spectral resolution (Rodler et al 1984;Hawkins & Andrews 1983).…”
Section: Com Formation In Experimentsmentioning
confidence: 99%
“…The IR features with relatively weak absorption coefficiency, which originate from the CH 3 deformation (ν 5 ) mode of acetaldehyde and CH 2 scissor (ν 6 ) mode of vinyl alcohol, are strongly blended with a broad H 2 O 2 peak Article number, page 5 of 17 Ethanol (CH 3 CH 2 OH) is clearly observed at 1041 cm −1 through its C-O stretching (ν 11 ) mode along with a relatively small feature at 1086 cm −1 (ν 10 ; CH 3 rocking mode) (Barnes & Hallam 1970;Mikawa et al 1971;Boudin et al 1998). The peak located at 2133 cm −1 can be assigned to the C=O stretching (ν 2 ) mode of ketene (CH 2 CO) (Hudson & Loeffler 2013). A tiny peak at ∼1744 cm −1 is tentatively assigned to the C=O stretching (ν 4 ) of acetic acid (Bahr et al 2006;Bertin et al 2011).…”
Section: Com Formation In Experimentsmentioning
confidence: 99%
“…CH 2 CO: CH 2 CO formation has been demonstrated experimentally by ice processing, with proposed formation mechanisms of either C 2 O hydrogenation (Maity et al 2014) or vinyl alcohol formation and decomposition (Hudson & Loeffler 2013). However, theory indicates that H addition to C 2 O is the dominant pathway (Garrod et al 2008).…”
Section: Com Formation Chemistrymentioning
confidence: 99%
“…[4] Its synthetic pathways in the ISM involvei nteraction of interstellar icy grains carrying methane and carbon monoxide with ionizing radiation at 10 K followed by sublimation of the ices in the hot core phase. [5,6] It was suggested that ketene forms molecules with ap eptide bond upon reactionw ith an amino acid;a nd in accordance with this, N-acetyl amino acids wasi dentified in meteorites such as Murchison. [7] More than half ac entury later,s ilylketenes were discovered.…”
Section: Introductionmentioning
confidence: 90%
“…Based on these spectroscopic studies, ketene was identified in the interstellar medium (ISM) toward the star forming region Sagittarius B2 via the 4 13 ‐3 12 , 5 15 ‐4 14 , and 5 12 ‐4 13 transitions between 81 and 101 GHz . Its synthetic pathways in the ISM involve interaction of interstellar icy grains carrying methane and carbon monoxide with ionizing radiation at 10 K followed by sublimation of the ices in the hot core phase . It was suggested that ketene forms molecules with a peptide bond upon reaction with an amino acid; and in accordance with this, N ‐acetyl amino acids was identified in meteorites such as Murchison…”
Section: Introductionmentioning
confidence: 99%